PENGARUH PEMBERIAN MINYAK ZAITUN Olive oil TERHADAP GAMBARAN HISTOPATOLOGI LAMBUNG TIKUS PUTIH (Rattus norvegicus) JANTAN GALUR Spargue dawley YANG DIINDUKSI ALKOHOL - Muhammad Reqza Pratama (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
Uncontrolled use of alcohol can cause variety damage to the gastric mucosa. Olive oil as an herbal plant is an important source for protecting and regenerating damaged gastric mucosa. This study is an experimental laboratory study with a post-test only control group design, which conducted at Animal House of Faculty of Medicine, University of Lampung by using 30 samples of male white rat (Rattus norvegicus) Sprague dawley which divided into 5 groups namely; negative control group (K-) only given distilled water 2ml / day, positive control group (K +) given alcohol 2.4ml / day for 14 days; treatment group 1 (P1) was given alcohol 2.4 ml / day and olive oil 0.27 ml / day for 14 days; treatment group 2 (P2) given alcohol 2.4ml / day and 0.54ml olive oil / day for 14 days; and treatment group 3 (P3) given alcohol 2.4 ml / day and 1.08 ml of olive oil / day for 14 days.Data were observed with the Kruskal-Wallis Non-Parametric Test, obtained p = 0,000 (p <0.05). The expected results obtained by Ho are expected. Statistical results with the Mann-Whitney test obtained also found a significant difference in each group.There is an influence of olive oil administration on histopathological decription of white rat gaster (Rattus norvegicus) male Spargue dawley strain alcohol-induced.